PARTICULARS OF CLINICAL POLYMORPHISM OF ACUTE EPILEPTIC SEIZURES. CLINICAL TELEMETRIC VIDEO-EEG EXAMINATION - S. A. Groppa; V. A. Kiosa; A. T. Hanganu (Эпилепсия и пароксизмальные состояния, 2016)
It is known than nearly two thirds of epileptic patients can be cured by proper therapy which can be prescribed after establishing of correct diagnosis. One of the most informative instrumental diagnostic techniques is video-EEG monitoring. This communication describes the role of clinical telemetric video-EEG examination in establishing and specifying the diagnosis of epilepsy.